Comparative analysis of the biological characteristics of three CV‐A10 clones adaptively cultured on Vero cells. Issue 8 (9th May 2022) - Zhao, Hong; Yang, Ting; Yue, Lei; Li, Hua; Xie, Tianhong; Xiang, Hong; Wang, Jie; Wei, Xingchen; Zhang, Yuhao; Xie, Zhongping
Abstract: Coxsackievirus A10 (CV‐A10) is a major pathogen that causes hand, foot, and mouth disease. There are no effective therapeutic drugs for CV‐A10 infection; therefore, CV‐A10 vaccines should be developed. Previously, we isolated a CV‐A10 strain (N25) that can be cultured on Vero cells. In this study, the N25 strain was plaque‐purified three times from Vero cells, and three clones were selected for adaptive culture. The three clones of the 5th, 12th, and 19th generations were compared and analyzed in terms of viral titers, plaque morphology, pathogenicity in suckling mice, and nucleotide and amino acid sequences of the complete genome. The infectivity titers of the three clones (P2–P22) were maintained at 6.5–7.0 lgCCID50 /ml. The three clones began to proliferate at 6 h and peaked at 36 h; the corresponding CCID50 was in the range of 10 6.5 –10 6.875 /ml, which gradually decreased. The suckling mice in the challenged group exhibited clinical symptoms such as paralysis of the limbs, which gradually worsened until death. The inactivated vaccines prepared using the three clones efficiently induced antigen‐specific serum antibodies in mice. There were eight nucleotide mutations in the three clones, which resulted in two and four amino acid substitutions in the VP3 and VP1 coding regions, respectively. The nucleotide and amino acid sequence homology between the three clones and N25 were 99.92%–100% and 99.78%–100%, respectively, indicating high genetic stability. Our findings provide a theoretical basis for screening CV‐A10 vaccine candidate clones.